Guinness world records 2002 - Edited By Cunningham, Antonia (British Guinness World Records, 2002)
An illustrated examination of records covering every field of human and non-human endeavor.
Include colored Illustration, Indexes
Keywords: World records -- Curiosities and wonders -- Questions and answers